Dynamical Behavior of Droplet Diffusion Flame of Blended Castor Oil with Metal Based Liquid Catalyst - Hendry Y. Nanlohy; Selcuk Sarikoc; Muji Setiyo (Automotive Experiences, 2024)
The tests revealed the exceptional combustion properties of a blended fuel consisting of castor oil and rhodium liquid (Rhl) as a highly effective homogeneous combustion catalyst. Our findings indicate that castor oil's unique molecular structure makes it an ideal fuel component, and the catalyst interacts with the fuel's triglycerides to enhance fuel properties and facilitate ignition.These findings support the pivotal role of the synthetic catalyst Rhl, which effectively reduces the binding forces within the triglyceride chain through polarization interactions. As a result, molecular bonds become more flexible, providing electrons with greater freedom of movement. Synthetic catalysts induce significant modifications in the triglyceride structure, increasing electron energy levels and enhancing the reactivity of fuel molecules, ultimately leading to improved fuel combustion efficiency. Integrating the Rhl synthetic catalyst also enhances fuel performance by reducing ignition duration and increasing the combustion rate. The elevated combustion temperatures of the fuel droplets highlight the effectiveness of promoting environmentally sustainable combustion processes.